GEORGIA-ROMANIA ECONOMIC COOPERATION AND THE NEW REGIONAL CHALLENGES - Lela JAMAGIDZE (EURINT, 2022)
The goal of the present paper is to analyze key issues in the economic relationship between Georgia and Romania. The analysis covers the dynamics of bilateral flows of goods, services and capital. It highlights the opportunities as well as the shared challenges that exist in the areas of trade and investment, transport and energy cooperation. Geographical proximity as well as a number of similarities in the economic structures and development levels of the two countries help them develop bilateral economic connections. Statistical analysis of the data on economic and institutional cooperation are used in order to show how Georgia and Romania are represented in the economic initiatives of mutual interest and how the two countries contribute to each other's positioning in the global and regional markets. Considering the current economic and security threats in the region, the study suggests that bilateral, country-to-country dimension of economic integration should be strengthened between the two countries in order to translate regional integration benefits into the real economic gains.